Accounting profit in spainish legislation - Aldeia, Susana (2019)
The main goal of this paper is to study the accounting profit in the spanish jurisdiction. For this purpose the accounting profit and its integration in accounting and tax legislation of Spain were analized. In accounting terms the study focus on the Comerce Code and Accounting law. On the one hand, the assumption of accounting profit in corporate income tax law and the significance of its economic periodization were investigated. The results show that the spanish Comerce Code recognizes a relevent role to accounting profit. It also recognizes that it is very important for the companies to give financial information about their economic lives. It establishes specific issues, such as the elements of the annual accounts, and how the net profit should be determined. On the other hand, an effort was made to understand and analyse the relevence of the periodization of the corporations´ economic life. It happens having as underlying the accrual basis' accounting principle. This may occur due to several economic, financial and legal reasons. Concerning the economic reasons it is necessary to define economic periods for management evaluation and the distribution of the results to the company's owners. Financially, the company has to assure all the financial needs to maintain its activity. In legal terms, it is important to determine tax periods that can establish the tax due by the entity's economic performance. The analysis of article 10 of the spanish corporate income tax law allows us to conclude that the spanish tax legislator recognizes the tax direct valuation method to determine the taxable profit. It means that the net profit determined under accounting rules is used to calculate the taxable basis that will be subjected to pay income tax by the national economic entities.